PEMBERDAYAAN ORANG MUDA KATOLIK PAROKI MUTING, KEUSKUPAN AGUNG MERAUKE DALAM BIDANG PASTORAL-KATEKESE DENGAN MODEL SHARED CHRISTIAN PRAXIS - Pranyoto, Yohanes Hendro (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2024)
The Catholic Youth (OMK) Empowerment Program in the pastoral-catechetical field, using the shared Christian Praxis (SCP) model, departs from the problem that young people are often used as pastoral objects of the church and not the subjects or pastoral actors themselves. We implemented this program as a workshop for four days using seminar methods, guided practice, simulation, evaluation, reflection, and follow-up. The target participants were 49 Catholic youths representing each station of the Muting Parish. The techniques for data collection are using questionnaires, observation, and documentation studies as portfolios of participants' work and also parish reports. The results: first, implementing SCP model catechesis training activities for OMK. Second, improving the quality of human resources (OMK) in terms of pastoral catechesis knowledge and skills, especially using the SCP model. Third, the formation of a work program and road map for parish-level catechesis themes for one year. The findings from this activity, especially the catechesis themes, which result from a social analysis by the activity participants, are very contextual and useful for the development of pastoral-catechetical programs in the parish. We hope the programs developed based on this theme mapping can answer the needs and problems of life of people in stations and parish. =========================================== Program pemberdayaan Orang Muda Katolik (OMK) dalam bidang pastoral-katekese dengan model shared christian praxis (SCP) ini berangkat dari permasalahan bahwa kaum muda sering kali dijadikan objek pastoral gereja dan bukan subjek atau pelaku pastoral itu sendiri. Program ini dilaksanakan dalam bentuk workshop selama 4 (empat) hari dengan metode seminar, praktik terbimbing, simulasi, evaluasi, refleksi dan tindak lanjut. Peserta sasaran adalah pengurus organisasi dan aktivis Orang Muda Katolik perwakilan dari setiap stasi berjumlah 49 orang. Teknik pengumpulan data menggunakan  kuesioner, observasi dan studi dokumentasi berupa portofolio karya peserta dan juga laporan paroki. Hasil dari program ini adalah; pertama, terlaksananya kegiatan pelatihan katekese model SCP bagi OMK. Kedua, peningkatan kualitas SDM (OMK) dalam hal pengetahuan dan keterampilan pastoral katekese khususnya dengan model SCP. Ketiga, terbentuknya program kerja serta road map tema katekese tingkat paroki untuk satu tahun. Hasil temuan dari kegiatan ini khususnya tema-tema katekese yang merupakan buah-buah pemikiran dan analisis sosial oleh peserta kegiatan sangat kontekstual dan bermanfaat bagi pengembangan program-program pastoral-katekese di tingkat paroki maupun stasi. Program-program yang dikembangkan berdasarkan pemetaan tema ini diharapkan dapat menjawab kebutuhan dan permasalahan hidup umat di stasi maupun paroki.